2017
DOI: 10.21037/tau.2016.11.17
|View full text |Cite
|
Sign up to set email alerts
|

Research in pharmacotherapy for erectile dysfunction

Abstract: Although oral phosphodiesterase-5 (PDE5) inhibitors are generally accepted as an effective therapy for erectile dysfunction (ED), men with ED from diabetes or radical prostatectomy respond poorly to these drugs. Many researchers have tried to develop novel therapeutics that target alternative molecular pathways. A group of therapeutics belongs to centrally acting agents that target dopamine and melanocortin receptors. The other one is the peripherally acting agents that target soluble guanylate cyclase, Rho-ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…A variety of pathological conditions, including microvascular dysfunction, peripheral neuropathy, and hormonal disturbances, are responsible for diabetic ED 2 . Because the pharmacological efficacy of phosphodiesterase type 5 (PDE5) inhibitors depends on endogenous nitric oxide (NO) production, a lack of bioavailable NO in diabetic men as the results of severe penile neurovascular dysfunction is the most important reason for poor responsiveness to these drugs 57 . Therefore, the development of a new therapeutic strategy that regenerates damaged penile neurovascular structure is needed.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of pathological conditions, including microvascular dysfunction, peripheral neuropathy, and hormonal disturbances, are responsible for diabetic ED 2 . Because the pharmacological efficacy of phosphodiesterase type 5 (PDE5) inhibitors depends on endogenous nitric oxide (NO) production, a lack of bioavailable NO in diabetic men as the results of severe penile neurovascular dysfunction is the most important reason for poor responsiveness to these drugs 57 . Therefore, the development of a new therapeutic strategy that regenerates damaged penile neurovascular structure is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the "Adi Subrata tion. 53 Relating to the urinary incontinence symptom, the questionnaire for urinary incontinence diagnosis (QUID) is recommended to be utilized for evaluating and diagnosing the type of incontinence in patients administering for urology surgery. 54 In line with the symptom domain, patients experiencing a low-tomoderate level of symptoms do not need any medical intervention.…”
Section: Characteristics Of the Environmentsmentioning
confidence: 99%
“…Patient-reported outcomes after RP were recently reviewed in the ProtecT trial and sexual dysfunction was found to significantly impact health-related quality of life (HRQOL) in patients with prostate cancer [ 6 , 7 ]. Treatments for ED in post-RP patients have inconsistent safety and efficacy profiles, and there remains an ongoing search for a well-tolerated and clinically durable therapeutic option for treatment-refractory men [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even with bilateral nerve-sparing and minimally invasive approaches to RP, some degree of CN injury (CNI) or neuropraxia is inevitable. Advances in technology and the understanding of penile neurobiology have led to neuromodulatory strategies targeting CN protection and regeneration [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation